Effect of Artificial Aging Protocols on Surface Gloss of Resin Composites - Rocha, Rafael Santos [UNESP]; Oliveira, Amanda Carvalho [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP]; Bresciani, Eduardo [UNESP] (Hindawi, 2017)
The purpose of this study was to evaluate the effect of aging protocols on surface gloss of composites. Cylindrical resin composite specimens (6 mm in diameter, 1 mm thick) were fabricated and divided into three groups (N=60): microfilled (MiFi), nanohybrid (NaHy), and nanofilled (NaFi). Specimens were distributed into four aging subgroups: thermocycling (5° to 55°C, 15,000 cycles); ethanol immersion (15 days); brushing (10,750 cycles); and light aging (216 h). Surface gloss readings (Novo-Curve, Rhopoint TM, England) were performed at baseline (R0) and after every one-third of aging protocols (R1 to R3). Data were submitted to one-way repeated measures ANOVA and Tukey's test (5%). Overall, surface gloss alterations were detected over time (p<0.001). Thermocycling reduced surface gloss, except for NaHy. Ethanol immersion resulted in surface gloss reduction after R1 for MiFi and NaFi, while reduction after R1 and R2 was detected for NaHy. For brushing, gloss reduction was detected after R1 and R3 for all composites. For light aging, gloss was reduced after R1 and R2 for MiFi and NaFi, while a reduction only after R1 was detected for NaHy. The studied aging protocols affect surface gloss differently, being material and aging therapy dependent. In general, the surface gloss is reduced with aging.